THE RELATIONSHIP BETWEEN FLIGHT HOURS, AGE, AND BODY MASS INDEX AND THE OCCURRENCE OF LOW BACK PAIN AMONG COMMERCIAL FIXED-WING PILOTS IN INDONESIA DURING THE COVID-19 PANDEMIC - Parmadi Komalajaya (CV Naskah Aceh, 2026)
Low back pain (LBP) is a common musculoskeletal complaint among workers, including commercial airline pilots. The aviation work environment is characterized by prolonged static sitting, whole-body vibration, mild hypoxia, low cabin humidity, and individual factors such as age and body mass index (BMI), all of which may contribute to the development of LBP. This study aimed to determine the prevalence of LBP and to analyze the association between total flight hours, age, and BMI with the occurrence of LBP among commercial fixed-wing pilots in Indonesia. An analytic observational study with a cross-sectional design was conducted at the Indonesian Civil Aviation Medical Center. The study population consisted of commercial fixed-wing pilots flying pressurized aircraft who underwent routine medical examinations (MEDEX). A total of 410 pilots met the inclusion criteria and were analyzed. Data were collected using structured questionnaires and medical records, including demographic characteristics, total flight hours, BMI, and LBP assessed using the Oswestry Disability Index (ODI). Data analysis included univariate, bivariate (Chi-square test), and multivariate logistic regression analyses. The prevalence of LBP among commercial fixed-wing pilots in Indonesia was 5.85%. No significant association was found between total flight hours, age, or BMI and the occurrence of LBP (p > 0.05). However, female pilots showed a significantly higher risk of LBP compared to male pilots (OR = 6.85; 95% CI: 1.47–31.81; p = 0.01). The prevalence of LBP among commercial fixed-wing pilots in Indonesia was relatively low. Total flight hours, age, and BMI were not significantly associated with LBP, whereas sex was the most influential factor. These findings highlight the importance of gender-sensitive ergonomic and occupational health strategies in the prevention of LBP among commercial pilots.